ESG: Integrating sustainability into business organizations - Krasin, Kremen (Edelweiss Applied Science and Technology, 2025)
In today's business world, ESG (Environmental, Social, and Governance) is an increasingly important component of corporate strategy. This approach combines three key aspects focusing on the company's sustainable and responsible management. Implementing ESG standards is important not only because it improves a company's image and sustainability but also because more investors and customers are looking to associate with companies that demonstrate a responsible attitude toward society and nature. Thus, ESG is not just a moral choice but a strategic necessity in the modern business environment. The article aims to review the tools related to ESG indicators that help organizations track their progress toward sustainability, the main concepts related to sustainable development and corporate sustainability, tools and methods for measuring corporate sustainability, and the integration of ESG into the company's strategy. The conclusion that must be drawn is that despite the difficulties and challenges associated with choosing the right tool to track the sustainability of business organizations, ESG is a valuable aid, providing them with important information. Timely interpretation of this information can be of great benefit to organizations, preventing their exposure to risks and shocks of an economic, social, or environmental nature. The application of tools to report on progress toward sustainable development contributes to the positive image of organizations and their contribution to the environment in which they operate.